Digital streak imaging of compressible flows. (January 2023) - Sridhar, V.; Hiraki, K.; Gai, S.L.; Kleine, H.
Highlights: Numerous applications in various compressible flow field investigations. The technique's filtering quality shows less prominent elements of a flow that are difficult to observe in the actual visualization records. Showing the evolution of flow features as a function of location and time by sequences of streaks obtained at different positions of the flow field. Inherent uncertainties in the measurements with this technique are highlighted. Abstract: This paper discusses a digital version of the traditional streak imaging technique combined with different flow visualization methods. The basic characteristics of the technique, its advantages and its shortcomings are presented alongside a number of applications in fluid mechanics. Streak images are useful to track and quantify the propagation or development of distinct flow features as a function of time. In addition, the appearance of a new trace, or the change of grey scale (or color in the case of polychrome visualizations), can be used to graphically reveal the location and instant of the onset of certain flow phenomena. In addition, the method also has a filtering quality that allows one to show less prominent elements of a flow that may be difficult to observe in the actual visualization records. A sequence of streaks obtained at different positions of the flow field can be used to track the evolution of flow features as a function of location and time. Some features of the digital technique are highlighted via a direct comparison with results from the literature.